Novel developments in field mechanics. Issue 98 (September 2016) - van Casteren, Adam; Venkataraman, Vivek; Ennos, A. Roland; Lucas, Peter W.
Abstract: Our aim is general: we want to illustrate how much can be gleaned from mechanical measurement in the field. We ask how mechanics may constrain foraging and feeding on both plants and animals, and how various aspects of mechanical behavior could affect the feeding choices that primates make. Here, we present novel methods for the measurement of the material properties and also the employment of tried and tested methods in novel settings. This review demonstrates how mechanical investigation methods can quantify the environmental factors affecting primate locomotion to and from food, which makes up a large part of a primate's daily energy budget. We indicate that, despite the accumulation of much data on the material properties of primate foods, the introduction of new methods is allowing researchers to pursue new avenues of research and change paradigms in primate feeding ecology. Field methods are presented that could aid in the understanding of the extra-oral processing of foodstuffs by primates and enrich further studies into cognition and culture surrounding these types of behavior. We conclude that the use of in-field measurements and a greater understanding of the physics of primate environments are vital and exciting themes integral to the continued understanding of primate evolution and biology.